SETA. (Helsinki : SETA, 1981)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks ; vanaf (1984) 1 : driemaandelijks ; vanaf (1991) 1 : tweemaandelijks
Redactie : Pl 45, 00251 Helsinki 25 ; vanaf (1983) 3 : 2 linja 10, 00530 Helsinki ; vanaf (1985) 2 Pl 55, 00531 Helsinki
Fins
Periodiek